(untitled) (Journal of Hama University, 2024)
The research aimed to identify the pragmatic language disorder among children with autism spectrum disorder according to some variables (years of rehabilitation, severity of the disorder), in some autism centers in Damascus. The research sample included (36) children with autism spectrum disorder, and to achieve the purpose of the research was the use of a scale (diagnosis of pragmatic language in children with autism spectrum disorder, prepared by Abdulaziz Al-Shakhes et al. 2015). during the conversation), and the search results were as follows: 1. The degree of prevalence of pragmatic language disorder among the research sample was medium. 2. There are statistically significant differences between the mean scores of the research sample individuals on the scale according to the variable years of qualification in favor of those whose qualification years are less than 3 years. 3. There are statistically significant differences between the mean scores of the research sample individuals on the scale according to the variable of severity of the disorder in favor of children with a severe degree, i.e. the higher the severity of the autism spectrum disorder, the higher the degree of the pragmatic language disorder.